Merry-making in old Russia and other stories - Popov, Evgenij Anatolʹevič 1946- (Northwestern Univ. Press, 1997)
Tragicomic tales set in the final days of the Soviet Union, where whether you work or don't, you still get paid, albeit not much. But vodka is cheap.
Teilausg.
Keywords: Short stories; Short stories, Russian